DIKSHA in Maharashtra Needs Assessment Report - Tara Stafford Ocansey; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
This report presents the key findings from a needs assessment conducted for the purpose of understanding the vision, goals, implementation plans and challenges for the successful rollout and uptake in Maharashtra of the National Digital Infrastructure for Knowledge Sharing platform, known as DIKSHA. DIKSHA was chosen as a topic for research due to its unprecedented potential to bring a wave of transformation in and access to the use of technology for instruction and teacher preparedness. In order to help ensure the program's success, it is imperative to document the processes from the beginning to understand what needs to be in place for such an ambitious platform to reach its maximum potential. The range of features envisioned for DIKSHA includes in-class resources, teacher training content, assessment aids, teacher profiles, news and announcements, and communication tools to foster teacher community. Maharashtra took on the massive task of integrating QR codes into every textbook at every grade level up to grade 10, in all languages of instruction in the 2018-19 academic year. To ensure every topic across every medium and grade level was equipped with content, the Maharashtra State Council of Education Research and Training (MSCERT) worked with non-profits including Leadership for Equity to hold a series of content creation workshops which are ongoing toward the aim of training 1,000 teachers across the state as content creators. Interviews and focus group discussions were held with stakeholders from MSCERT, the MSCERT textbook publishing arm Balbharati, DIECPD officials and teacher support staff from several districts including Satara and Aurangabad districts, NGOs contributing in various ways including Leadership for Equity and Rotary, and teachers from schools in Wai and Pune. (...)
Keywords: 330